Mobile, secure, and programmable networking : second International Conference, MSPN 2016, Paris, France, June 1-3, 2016, Revised selected papers /: second International Conference, MSPN 2016, Paris, France, June 1-3, 2016, Revised selected papers. (2016) - Unknown
No abstract available